Relationship between periodontal parameters and non-vital pulp in dental clinic patients: a cross-sectional study - Tomotaka Kato; Natsuki Fujiwara; Ryutaro Kuraji; Yukihiro Numabe (BMC, 2020)
Abstract Background Endodontic diseases, such as apical periodontitis, communicate with periodontitis and mutually exacerbate them. However, it remains unclear whether pulp condition is a risk factor for periodontal disease. The purpose of this retrospective study was to examine relations between pulp condition and periodontal parameters in Japanese patients who visited a general dental clinic. Methods Patients who visited a Japanese general dental clinic from 2016 to 2018 and aged 18 to 81 years were analyzed. Periodontal parameters, tooth condition, and general status of all teeth excluding third molars at the initial visit to the clinic were abstracted. A total of 7105 teeth were analyzed in this study by multiple classification analysis and the Mann-Whitney U test. We also performed a sub-analysis of non-vital teeth, which evaluated the presence or absence of unfavorable root canal obturation and apical periodontitis diagnosed by X-ray. Results Significant relations between periodontal parameters and non-vital pulp were observed by multiple logistic regression analyses (odds ratio = 1.48; 95% CI = 1.03-2.14) and multiple linear regression analysis (p < 0.001). Significant relations between unfavorable root canal obturation tooth with periodontal pocket depth (p = 0.00837) and BOP (p = 0.0145) were also observed by the Mann-Whitney U test. Conclusions We demonstrated potential relations between periodontal disease and non-vital pulp.